Synthetic peptides as probes for protein interactions and as antigenic epitopes - Närvänen, Ale (1990)
In this study synthetic peptides have been used both as antigens in immunological studies, as well as probes in a study of protein interactions. Rabbit antibodies to the synthetic peptide sp23 derived from a cloned sequence of human endogenous retroviral gene erv-1 were used in a search for the expression products in human cell cultures and tissues. The cross-reactivity of the anti-peptide antibodies led to the detection of a novel protein from human chorio-carcinoma cell line. This protein of Mr 75 000 was purified by using conventional biochemical methods and the purification steps were monitored with anti-sp23 antibodies. Synthetic peptide deduced from the cDNA sequence of the transmembrane protein gp41 of human immunodeficiency virus HIV-1, the causative agent of AIDS, have been used as antigen detecting human antibodies to HIV-1. In clinical studies, strong antibody responses against this peptide were found during the early stages of HIV infection, including cases with seroconversion. The antibody level tended to decrease in the sera at the ARC and AIDS stages of HIV infection. Human antibodies to a synthetic peptide containing this sequence were affinity-purified and tested using various immunological methods. These affinity-purified antibodies did not react with the gp41 protein, suggesting that this epitope is partially or totally buried in the molecule and may only be exposed during antigen processing in vivo in the HIV-infected individuals. Laminin is a 1000 kd extracellular matrix protein, that has a multidomain structure with various functions such as neuronal cell-adhesion and the promotion of brain development and neurite outgrowth. In studies to locate functional regions in laminin molecule, synthetic peptides have been used in biological studies in vitro. A synthetic peptide derived from the maximally amphipathic region in the carboxy terminal part of B2 chain of laminin showed neurite outgrowth-promoting activity in neuronal cell cultures.